Implementasi Emergency Fund dan Investasi Saham Syariah bagi Wirausaha Muda untuk Memperkuat Tata Kelola Keuangan dalam Menghadapi Krisis Akibat Covid-19 - Dito Rinaldo; Vina Anggilia Puspita (Universitas Muhammadiyah Surakarta, 2022)
This community service program aims to improve MSME financial management, by increasing knowledge of financial planning and sharia stock investment. Participants are STIE EKUITAS entrepreneurial students consisting of 21 entrepreneurs. The service method adopts the concept of Plan, Do, Check, Action (PDCA), problem solving 101 (Ken Watanabe) and the capital market education model which is the result of the previous team’s research. The results of the PKM evaluation showed an increase in knowledge, but in advanced and practical material the knowledge of participants did not increase significantly. In the next service program, a more integrated and structured educational model is needed, involving various parties such as practitioners, academics, communities, the Indonesia Stock Exchange and securities companies, so that the program is more effective.